Pengaruh Pengalaman Auditor, Keahlian Auditor, Etika Auditor, Dan Tekanan Anggaran Waktu Terhadap Kinerja Auditor - Rachmat Arif; Novita Sari (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to obtain empirical evidence regarding the influence of auditor experience, auditor expertise, auditor ethics, and time budget pressures on audit performance. In this study, there are 5 variables, namely auditor performance as a dependent variable while auditor experience, auditor expertise, auditor ethics, and time budget pressure as independent variables. The subject of this study was an auditor who worked at a public accounting firm in the West Jakarta Region. The number of samples in this study was 6 Public Accounting Firms and 70 respondents. Data collection was carried out by distributing questionnaires using a 5-point likert scale. This study in analyzing the data using multiple linear regression with the help of the Statistical Product for Service Solution (SPSS) program version 26. The results showed that auditor experience and auditor ethics did not have a significant effect on auditor performance, while auditor expertise and time budget pressures had a significant effect on auditor performance.